Casein-dextran complexes subjected to microfiltration: Colloidal properties and their corresponding processing behaviors. (May 2022) - Peng, Binsha; Li, Zihe; Xiong, Qinmei; Wu, Chongde; Huang, Jun; Zhou, Rongqing; Jin, Yao
Abstract: In this work, protein-polysaccharide complexes were subjected to microfiltration, a typical multi-force process. Particle and flow properties of casein-dextran complexes were analyzed in various solution conditions, and their processing behaviors of microfiltration, elucidated by resistance, fouling propensity and interaction with porous polymer surface, were also investigated. Results suggested that the medium pH and the casein/dextran ratio had significant influences on particle and rheological properties of such complexes, and then led to notable different processing behaviors of microfiltration. Being subjected to the process of microfiltration, casein-dextran complexes of monomodal particle size distribution formed a compact and smooth cake layer on the membrane surface, which was resistant, and later-coming particles were easy to deposit on previously settled ones. Therefore, the growth rate of fouling was high and the transition of complex/membrane interaction regime was quite fast from complete pore blocking to cake formation mechanism. On the contrary, the complex of multimodal particle size distribution may easily form a loose and rough layer on the membrane surface while partially blocked the membrane pore entrance, which was less resistant. Consequently, the growth of such fouling layer was hindered, which then resulted in the slow-down of the transition from one regime to another (from complete pore blocking to standard pore blocking then to intermediate pore blocking mechanism). This work provides generalized and pertinent guidance for microfiltration of protein-polysaccharide complexes. Highlights: Intrinsic properties of casein-dextran complexes were correlated to their processing behaviors. Properties/processing behaviors of casein-dextran complex strongly depend on medium pH. Particle properties of complex dominate the fouling growth and structure in MF. Medium pH governs the transition of pore blocking mechanism. Presence of polysaccharide may be favorable for the process efficiency.